Sleep disturbance as part of the neurofibromatosis type 1 phenotype in adults. Issue 6 (1st May 2013) - Leschziner, Guy D.; Golding, John F.; Ferner, Rosalie E.
Abstract Neurofibromatosis type 1 (NF1) is an autosomal dominant condition with a wide array of neurological complications, including cognitive dysfunction, tumors, malformations, neuropathy, neurovascular disease, and epilepsy. Many of these complications may impact on sleep quality and cause sleep disturbance. Previously sleep disturbance in NF1 has been specifically addressed solely in children. We performed a prospective study of sleep quality in 114 consecutive out‐patients with NF1 attending our national neurofibromatosis service. The Epworth sleepiness scale (ESS) and the Pittsburgh sleep quality index (PSQI) were administered, and information was obtained from patient records on drugs potentially impacting on sleep, complications directly affecting sleep and employment status. The mean ESS was 6.8, and 21% had an abnormally high ESS of 10 or more. The mean global PSQI score was 8.4 (norm mean 2.67), with abnormally high scores in all sleep domains. Thirty‐nine patients had a bed partner and 54% reported features suggestive of periodic limb movements of sleep, 43% had features suggestive of obstructive sleep apnoea, and 10.8% experienced confusion on waking. There was no evidence of phase shift. The ESS did not correlate with the PSQI, but unemployment status was associated with worse global PSQI score and multiple domain sub‐scales of sleep quality in the PSQI. We conclude that sleep disturbance and poor sleep quality are significantly more frequent in the adult NF1 patient population. It is likely to be multi‐factorial, related to pain, anxiety, depression, cognitive issues, and organic sleep pathology. We recommend careful assessment of patients to determine underlying triggers and possible treatment strategies. © 2013 Wiley Periodicals, Inc.